High-purity hydrogen production from dehydrogenation of methylcyclohexane catalyzed by zeolite-encapsulated subnanometer platinum-iron clusters - Zhe He; Kailang Li; Tianxiang Chen; Yunchao Feng; Eduardo Villalobos-Portillo; Carlo Marini; Tsz Woon Benedict Lo; Fuyuan Yang; Liang Zhang; Lichen Liu (Nature Communications)
Abstract Liquid organic hydrogen carriers (LOHCs) are considered promising carriers for large-scale H2 storage and transportation, among which the toluene-methylcyclohexane cycle has attracted great attention from industry and academia because of the low cost and its compatibility with the current infrastructure facility for the transportation of chemicals. The large-scale deployment of the H2 storage/transportation plants based on the toluene-methylcyclohexane cycle relies on the use of high-performance catalysts, especially for the H2 release process through the dehydrogenation of methylcyclohexane. In this work, we have developed a highly efficient catalyst for MCH dehydrogenation reaction by incorporating subnanometer PtFe clusters with precisely controlled composition and location within a rigid zeolite matrix. The resultant zeolite-encapsulated PtFe clusters exhibit the up-to-date highest reaction rate for dehydrogenation of methylcyclohexane to toluene, very high chemoselectivity to toluene (enabling the production of H2 with purity >99.9%), remarkably high stability (>2000 h) and regenerability over consecutive reaction-regeneration cycles.